FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA CAKUPAN IMUNISASI TT (TETANUS TOKSOID) PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS MELINTANG KOTA PANGKALPINANG : Jonnimar (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2021)
Tetanus Toxoid (TT) immunization is the process of forming a person’s immune system as a form of prevention from Tetanus neonatorum infection, which infected by Clostridium tetani bacteria that occurred from childbirth and unclean and unsterile umbilical cord cutting. A low coverage of Tetanus Toxoid (TT) immunization for pregnant mothers in 2018-2020 in the work area of Melintang Public Health Center in Pangkalpinang City. The purpose of this study is to understand the relationship between the education of pregnant mothers, knowledge of pregnant mothers, attitude of pregnant mothers, role of health workers, and husband’s support towards the low coverage of Tetanus Toxoid (TT) immunization in pregnant mothers in the work area of Melintang Public Health Center in Pangkalpinang.This study used a cross sectional research design using the Chi Square test and the sampling technique was Simple Random Sampling with data collection using interview method through questionnaire. The study population was 670 pregnant mothers. The research sample was 94 respondents. Study results point out that there was a significant relationship between education of pregnant mothers (p value = 0.005), attitude of pregnant mothers (p value = 0.002), role of health workers (p value = 0.005) and husband’s support (p value = 0.009) but there was no significant relationship between the knowledge of pregnant mothers (0.065) and the low coverage of Tetanus Toxoid (TT) immunization in pregnant mothers in the work area of Melintang Public Health Center in Pangkalpinang. The factor that tends to be dominant is the attitude of pregnant mothers with POR = 4,556. It is recommended that the public health center increase the intensity of counseling, provide health service post, carry out periodical screening to record pregnant mothers who have or have not taken TT immunization. For the community especially pregnant mothers, it is recommended to take TT immunization during pregnancy with a minimum of two times TT immunization injections, and be active in pregnancy check-up.